Evaluasi, Penilaian, Tes, dan Pengukuran dalam Pembelajaran: Analisis Konseptual dan Implikasinya terhadap Praktik Pendidikan - Rismayana Johan; Saridah; Maulina M (Yayasan Dharma Lentera Khatulistiwa (MALEWA), 2026)
Evaluation in learning is a crucial part of the educational process because it serves to determine the level of student success and the effectiveness of the learning process that has been implemented. In the world of education, the term